CHARACTERISTICS OF GASTRONOMY ADVERTISING TEXTS AND ITS STUDY (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
Today, gastronomic advertising texts are becoming an important part of human life. In addition, it is worth noting that gastronomic advertising texts have formed a culture creator in society and are seen as a force that increases the demand of consumers for food products. Of course, the main influence of gastronomic advertising, whether oral or written, is the language and its internal possibilities. Gastronomic advertising texts in Uzbek, as in other languages, differ sharply from other types of texts with their specific features and methods of expression. In turn, several types of gastronomic advertising texts are classified. This article provides information about gastronomic advertising texts and their types, as well as the importance of language tools in such texts